MICROSTRUCTURE DESIGN AND MECHANICAL PROPERTIES ANALYSIS OF POROUS BONE WITH NEGATIVE POISSION’S RATIO (MT) - YE JianHua; LI DongYu; LIN Jia; ZENG ShouJin; WEI TiePing; XU MingSan (Jixie qiangdu)
In view of the large difference between the elastic modulus of human bone structure and metal materials and the difficulty of control, the goal is to reduce or eliminate the “stress shielding” effect in a wide span, introduce a negative Poisson’s ratio metamaterial with an unconventional deformation mechanism, carry out the design and experimental research of porous microstructure with wide span and low elastic modulus. Based on the negative Poisson’s ratio auxetic structure unit, the three-dimensional cellular porous microstructures with different control parameters and porosity were designed.Experimental samples were prepared by selective laser melting. The variation rules between mechanical properties and structural parameters such as strength and elastic modulus were revealed through compression tests, and the matching degree of negative Poisson’s ratio microstructure and human bone was evaluated. The experimental results show that the auxetic structure has good manufacturability, and the forming quality is correlated with the concave angle and porosity.The mechanical properties of negative Poisson’s ratio auxetic structure are highly dependent on the geometric structure and porosity of the cell.Compared with the positive Poisson’s ratio structure, the auxetic structure with negative Poisson’s ratio has lower elastic modulus and similar yield strength under the same porosity, and can control the 316 L stainless steel bone material with wide span elastic modulus by 0.47 GPa～1.75 GPa.Therefore, the negative Poisson’s ratio auxetic microstructure has potential advantages in the application of human bone structure.